Pengembangan Flipbook Materi Table Set Up Pada Mata Kuliah Food and Beverage Service and Bar di Universitas Pendidikan Ganesha - Liantini, Kadek Wina; Ariani, Risa Panti; Sukerti, Ni Wayan (Universitas Mathla'ul Anwar Banten, 2025)
In general, this study aims to identify the stages of developing a flipbook using the (R&D) method with the 4D development model (define, design, development, disseminate) in the Food and Beverage Service and Bar course, specifically on the topic of table set up. The study produced a flipbook as a learning medium, examined its feasibility, and analyzed students’ responses toward its use. The research sample consisted of 52 fourth- and sixth-semester students who had completed the Food and Beverage Service and Bar course. Data were collected through questionnaires using a Likert Scale, which were distributed to experts and respondents, and then analyzed using descriptive qualitative and quantitative techniques. The results of the study indicate that the flipbook on Table Set Up developed with the 4D model was evaluated as “very feasible” by experts, with scores of 94.20% from content experts, 96.37% from instructional media experts, and 96.37% from instructional design experts. The final overall score reached 93.87%, while students’ responses were categorized as “very good.”It can be concluded that the Table Set Up flipbook developed with the 4D model was declared very feasible by experts and received a very good response from students, making it effective as a learning medium in the Food and Beverage Service course.